Bioremediation to increase the ex-mining land reclamation in Indonesia. Issue 1 (1st December 2022) - Rosa, E; Sufardi, S; Syafruddin, S; Rusdi, M
Abstract: Bioremediation was method to processed using microorganisms such as the bacteria, fungi (mycoremediation), yeast, algae, and enzymes produced by these microbes to clean or neutralize chemicals and the raw material cement to alternative in dealing with environmental control. Furthermore, the reclamation was improve the post-mining environmental area to produce a better ecosystem environment, than it was appearance. Bioremediation and reclamation was mutual support method to maintain the ex-mining land. This study method used the literature review method. In the result, we are describe the chemical bioremediation principles included with the anoxic lime to utilizing sulphide reducing bacteria, the landscaping with compost to increase the ability of the soil to hold water and contains a relatively high element of C a source of energy microbes and the environmental modification to add the electron acceptor nutrients. Then, other activities that to increase ex-mining land services due to other mining activities was reclamation. The reclamation activities can be seen from the quality of the land which is a very important environmental component. Where open-pit mining will also result in changes in the physical, chemical, and biological properties of the soil, so it is necessary to manage ex-mining land. We are represent the reclamation principles, i.e. topsoil conservation was the avoid subsoil mixtures was contain the elements, the land arrangement was improve the condition of the landscape nature with the closing the dug holes, the sediment management and erosion control and the heavy metal management was reduce the heavy metal content and that was need to select the plant species that tolerant of heavy metals.